Cover Image, Volume 56, Issue 2. (2nd April 2018) - Reut, Michał; Matsumura, Yoko; Kozlowski, Marek W.; Beutel, Rolf Georg
Abstract : The cover image, by Michał Reut et al., is based on the Short Communication Bizarre mating in the entimine weevil Polydrusus picus, DOI10.1111/jzs.12194 .